Aleitamento materno na perspectiva da mulher/usuária da Rede Mãe Paranaense - Sousa, Layna Nunes Nascimento Mendes Franco de (2019)
Introduction: In 2012, Paraná created the Rede Mãe Paranaense (RMP). Since the first public policies of attention to maternal and child health, the aim was to encourage breastfeeding. In health systems, health care providers influence and support decisions about food at critical times. To be successful in exclusive breastfeeding and reduce early weaning, it is necessary to develop joint actions during prenatal care, puerperium, childcare and home visits. Methods: This is a quantitative, descriptive, cross-sectional research that was developed in three Health Regions (RS): 9th RS, 10th RS and 17th RS in the state of Paraná. The population was constituted by sample calculation, of the non-probabilistic type, for convenience, by the users attended at the Reference maternity hospitals for childbirth in the RMP of the three RS. Interviews were conducted with the users at the maternity hospital. The data collected from 1270 patients were tabulated using Microsoft Excel®. For questions related to specific objectives, the Chi-square test for K proportions was performed, with α = 5% of significance, to identify whether there is a statistical difference between the frequencies of the answers in each question. All analyzes were performed using the licensed program XLStat Version 201. .Results: Most of the women who participated in the research delivered the baby in the 17th RS. Most were between 16 and 25 years old (n = 650; 51.18%), had a partner (n = 1130; 88.98%), had an unpaid occupation (n = 685; 53.94%) and completed high school (n = 457; 35.98%), the majority declared having only one child with their current partner (n = 531; 41.81%) and were primiparous (n = 498; 39.21%). Most performed prenatal care at the UBS (n = 1029; 81.02%), but did not participate in groups of pregnant women (n = 1039; 81.81%). Conclusion: Breastfeeding is a complex practice that involves social and cultural issues that influence a woman's decision to breastfeed or not. Therefore, it is important to carry out breastfeeding promotion activities since prenatal care. Health professionals are needed to encourage and support mothers and to receive adequate training to transmit knowledge and skills to pregnant women and mothers. In this research, the 9th SR presented the worst results in relation to the other RS, which reinforces the need to improve the qualification of professionals, but, above all, reinforces the urgency of a different view of public authorities on the border regions with the creation of specific public policies for such regions.